AKTIVITAS ANTIBAKTERI DARI EKSTRAK KASAR BAKTERI YANG BERASOSIASI DENGAN SPONGE Acanthostrongylophora sp. - Ginting, Elvy L; Warouw, Veibe; Suleman, Rizal W (Sam Ratulangi University, 2010)
Sponges have a potential to produce bioactive compounds. Their ability to do it since there is a symbiotic relationship with microorganisms in these bacteria. Because of this critical role, the bacteria symbiotic with sponge allegedly have great potential in terms of producing bioactive compounds that have been isolated from sponges (Lee, et al, 2001). In this study, using bacterial culture preparations isolated from the sponge, Acanthostrongylophora sp., the bacterial isolates were tested for their antibacterial activities using a well diffusion test. Based on the antibacterial activity test, the bacterial isolates known as BPO (shaped wavy white dots) and BPB (white threadlike have a certain type of thread) had antibacterial activity. ODS had a broad spectrum as potent against all three types of tested bacteria (Vibrio cholerae, Staphyloccocus aureus, Bacillus subtillis).